Multibeam bathymetry raw data (Atlas Hydrosweep DS 2 echo sounder entire dataset) of RV METEOR during cruise M57/1 - Rüdiger Schacht; Volkhard Spieß; Ralph R Schneider (PANGAEA, 2025)
Raw bathymetry data were collected using the ship extquotesingles own Atlas Hydrosweep DS2 multibeam echosounder during the RV METEOR cruise M57/1. The cruise took place between 2003-01-20 and 2003-02-08 (Capetown, South Africa - Walvis Bay, Namibia). Combined bathymetric measurements and sub-bottom (Parasound) profiling were performed to map the distribution of the Holocene mudbelt and Quaternary sediments as well as to select coring locations. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. No ancillary sound velocity profiles (SVP) data from the cruise are archived at the BSH, thus no SVP files are added to this dataset. Data are unprocessed and therefore can contain incorrect depth measurements (artifacts). Data can be processed e.g. with the open source software package MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, http://www.mbari.org/products/research-software/mb-system/, 2022).